Gender disparities in match performance at FIFA world cups: More direct play, less off-ball movement, and less pressing in women`s matches - Ju, W.; Kim, B.; Lee, J.; Choi, S. (International Journal of Performance Analysis in Sport, 2025)
This study examined gender differences in physical and technical/tactical performance of teams during the FIFA World Cup Qatar 2022 (MWC) and FIFA Women`s World Cup Australia & New Zealand 2023 (WWC). A total of 111 matches (n*=*222 game observations) were analysed using an optical tracking system. Compared to the MWC teams, the WWC teams covered 4% less total distance and relative distance per minute (p*<*0.0001; effect size [ES]: 0.8) and reached 9% lower top speeds (p*<*0.0001; ES: 3.5). The WWC teams adopted a more direct style, executing 25% more line breaks "over" the opposition (p*<*0.0001; ES: 1.1), while completing 14% fewer passes (p*=*0.0005; ES: 0.5) with 10% lower pass/line break completion rates (p*<*0.0001; ES: 1.0-1.1). The WWC teams made 34-39% fewer offers/movements to receive the ball (p*<*0.001; ES: 1.1-1.3) and received the ball 43% less frequently (p*<*0.0001; ES: 1.3). The WWC teams applied 21% less defensive pressure (p*<*0.0001; ES: 0.8). However, the WWC teams performed 13-38% more defensive actions (tackles, second balls etc.) than the MWC teams (p < 0.0001; ES: 0.3-1.8). These findings highlight the distinct physical and technical/tactical demands in men`s and women`s international football and support the need for gender-informed training strategies, talent development and context-informed interpretation.